2021
DOI: 10.3389/fmolb.2021.674632
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/dCas9-Mediated Parkin Inhibition Impairs Mitophagy and Aggravates Apoptosis of Rat Nucleus Pulposus Cells Under Oxidative Stress

Abstract: ObjectiveThe aim of this study is to explore the role of Parkin in intervertebral disk degeneration (IDD) and its mitophagy regulation mechanism.Study design and methodsRat nucleus pulposus (NP) cells were stimulated with hydrogen peroxide (H2O2) to a mimic pathological condition. Apoptosis and mitophagy were assessed by Western blot, terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay, and immunofluorescence staining. The CRISPR–dCas9–KRAB system was used to silence the expression of Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Although the regulation of mitophagy has shown great potential in the treatment of bone diseases, there are still a series of issues to be further clarified: (1) the characteristics of different stages of drug-activated mitophagy need to be further elucidated, including labeling damaged mitochondria, autophagosome formation, lysosome and autophagosome fusion, and exocytosis; (2) although many signaling pathways have been found to be involved in the mediation of mitophagy, the precise regulatory mechanism needs further research to discover specific effective drug targets; (3) many studies are limited by observing mitophagy in cells at only one time point. More experimental validation with different time points or a long time after regulation of mitophagy should be performed to identify potential biomarkers, targets, or long-term effects; (4) the results of some studies are contradictory, reflecting that the pro-survival or pro-death effect of mitophagy on cells or tissues is related to the difference in the type, timing, and extent of cells being stimulated and the surrounding microenvironment [ 86 , 87 ]. Therefore, how to reasonably regulate the level of mitophagy according to different diseases is a key direction of future research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the regulation of mitophagy has shown great potential in the treatment of bone diseases, there are still a series of issues to be further clarified: (1) the characteristics of different stages of drug-activated mitophagy need to be further elucidated, including labeling damaged mitochondria, autophagosome formation, lysosome and autophagosome fusion, and exocytosis; (2) although many signaling pathways have been found to be involved in the mediation of mitophagy, the precise regulatory mechanism needs further research to discover specific effective drug targets; (3) many studies are limited by observing mitophagy in cells at only one time point. More experimental validation with different time points or a long time after regulation of mitophagy should be performed to identify potential biomarkers, targets, or long-term effects; (4) the results of some studies are contradictory, reflecting that the pro-survival or pro-death effect of mitophagy on cells or tissues is related to the difference in the type, timing, and extent of cells being stimulated and the surrounding microenvironment [ 86 , 87 ]. Therefore, how to reasonably regulate the level of mitophagy according to different diseases is a key direction of future research.…”
Section: Discussionmentioning
confidence: 99%
“…Parkin signaling plays a key role in mitophagy induction, which regulates the ubiquitination of mitochondrial outer membrane proteins and promotes dysfunctional mitochondrial degradation [ 87 ]. In addition, a meta-analysis of 4600 people by Williams et al [ 108 ] found CpG island methylation of the PARK2 gene (encode Parkin protein) promoter in IVDD patients, indicating that Parkin signaling is closely related to IVDD.…”
Section: Mitophagy and Intervertebral Disc Degenerationmentioning
confidence: 99%
See 1 more Smart Citation